The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/2237-101x0183404
|View full text |Cite
|
Sign up to set email alerts
|

Esportes nos confins da civilização: Mato Grosso, 1920-1930

Abstract: RESUMOAnalisando livros de viagem e de memorialistas, alguns documentos oficiais e jornais publicados no Mato Grosso, disponíveis nos acervos do Arquivo do Estado do Mato Grosso, da Biblioteca Nacional do Rio de Janeiro e do Arquivo do Exército, este artigo descreve e interpreta a história dos esportes no Mato Grosso na década de 1920, período que corresponde a um considerável processo de expansão social e geográfica dessas práticas na região. O desenvolvimento histórico do esporte no Mato Grosso, articulado a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
1
0
4
Order By: Relevance
“…When seeing the region of Montes Claros, in the hinterland and detached from the great centres of the nation, the reflection of what happened in the Capital is observed, radiating to the upstate city. In this analysis, we evaluate the warning made by Dias 19 : '[…] a research on the history of sports in some rural region in the countryside tends to reproduce, sometimes even in an exaggerated way, the same general conclusions of studies conducted in large urban centres'. However, it is identified that Minas Tennis Club, from Belo Horizonte, did, in fact, influence the design and execution of the Montes Claros Sports Square (Figure 5), playing a reference role.…”
Section: Resultsmentioning
confidence: 99%
“…When seeing the region of Montes Claros, in the hinterland and detached from the great centres of the nation, the reflection of what happened in the Capital is observed, radiating to the upstate city. In this analysis, we evaluate the warning made by Dias 19 : '[…] a research on the history of sports in some rural region in the countryside tends to reproduce, sometimes even in an exaggerated way, the same general conclusions of studies conducted in large urban centres'. However, it is identified that Minas Tennis Club, from Belo Horizonte, did, in fact, influence the design and execution of the Montes Claros Sports Square (Figure 5), playing a reference role.…”
Section: Resultsmentioning
confidence: 99%
“…Todavia, algumas pesquisas realizadas no campo da historiografia do esporte brasileiro, na última década, têm buscado analisar historicamente a gênese do esporte em contextos rurais e periféricos, algo Topoi (Rio J. ), v. 25: e20220071, 2024 http://dx.doi.org/10.1590/2237-101X02505512 que nos trouxe elementos importantes para questionar a dicotomia centro-periferia, que é, em última instância, justificada pelos produtos da modernidade (DIAS, 2017;DIAS, 2019;SOUZA, 2020;NUNES, 2021).…”
Section: Associativismo E Esporte No Brasilunclassified
“…Nesse cenário, de acordo com Moraes e Silva, 14 observa-se, inclusive, uma maior valorização e estruturação do comér-8 DIAS, Cleber Augusto Gonçalves. Esportes nos confins da civilização: Goiás e Mato Grosso, c. 1866-1936. 7Letras, 2018 DIAS, Cleber Augusto Gonçalves; SOUZA, Elisa Salgado de.…”
Section: Introductionunclassified